THE RECONSTRUCTION OF RELIGIOUS EDUCATION INTO COMMUNITY’S LEGAL LIFE - Suryono, Hassan (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
The aim of this study was to elaborate how the religious education can be implemented to the community life as the reference and norm of behavior in their life. Religious education developed in legal order remained to be needed inexplicitly. There is a tendency that the community wanted to organize their life corresponding to the religion. For making the religion to be alive, the state’s leadership and participation is needed to regulate it. The constructed religion value in community behavior manifested in legislation will ensure the presence of both law certainty and law enforcement. Thus, religion and law containing regulations and prohibitions will bind to everyone, either ordinary people or ruler. The religion becoming the universal foundation of life. So, there should be an identification and verification of shared religion values before they are constructed to be law in the plural community life.***Tujuan dari penelitian ini adalah untuk menguraikan bagaimana pendidikan agama dapat diterapkan untuk kehidupan masyarakat sebagai referensi dan norma-norma perilaku dalam kehidupan mereka. Pendidikan agama dikembangkan di tengah masyarakat hukum secara tidak eksplisit. Ada kecenderungan bahwa masyarakat ingin mengatur hidup mereka sesuai dengan agama. Akan tetapi peran serta negara tetap diperlukan untuk mengatur itu, dimana nilai-nilai agama diwujudkan dalam undang-undang, sehingga dapat dipastikan adanya kehadiran hukum agama dan hukum positif untuk tegaknya suatu tatanan hukum. Hal ini karena agama dan hukum mengandung peraturan dan larangan akan mengikat semua orang, baik orang biasa atau penguasa. Agama juga menjadi tumpuan hidup yang bersifat universal. Oleh karenanya, diperlukan identifikasi dan verifikasi terhadap nilai-nilai agama yang universal sebelum menjadi hukum yang disepakati di dalam masyarakat plural.